Analisis Hukum Penerapan Sanksi Pidana Penyalahgunaan Narkotika Oleh Hakim Ditinjau Dari Sema Nomor 4 Tahun 2010 Di Kota Palembang - Choirul Nur Akrom; R. Octavianus; Nirwan; Muhammad Arif Syah Putra (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
Law enforcement against drug abuse in Palembang has been carried out in accordance with SEMA No. 4 of 2010, but court decisions are still dominated by prison sentences rather than rehabilitation. Data from the National Narcotics Agency (BNN) for 2020-2022 shows that 1,433 drug addicts were detected, but only 100 were processed to the investigation stage. The main obstacles to implementing Law No. 35 of 2009 include limited public participation and understanding of the BNN's role, social stigma toward drug users, and insufficient rehabilitation facilities. Many families are reluctant to cooperate out of fear that their family members will be imprisoned, even though there are opportunities for rehabilitation or outpatient treatment. This situation restricts the authorities' ability to address drug-related cases.